Usability and Suitability of Blackboard Learn with the Perspectives of the Faculty Members - ALMANSOORI, AFRA GHAREEB (2021)
This study is aimed at providing insights into the main prospects, obstacles, and best practices of technology integration for the effective implementation of a smart remote learning system in the United Arab Emirates (UAE). Such insights are obtained through examining the usability and suitability of Blackboard Learn (BBL) among faculty members of the biggest and second oldest higher education institution in the UAE. The main research question is – ‘what are the trends and developments accounted for in the literature on technology integration in higher educational institutions in the UAE?’ Two main groups of theories were consulted in this study. Broad theories such as Scaffolding, Zone of Proximal Development ZPD, and Activity Theory, and specific theories like TPACK, Bloom's digital taxonomy, and Connectivism Learning Theory are referred to in order to draw suitable conclusions. The rationale of this study is to discuss the data gathered to improve the faculty's professional experiences of technology integration. The rationale can also be explained by examining the progress of implementation of BBL in the UAE. Technology integration is a critical aspect of the educational industry as per the guidelines given by the governments to achieve the goals of the National Agenda of the UAE Vision 2021 to transform the UAE into a smart country. Therefore, examining the progress of such integration is significant. A mixed methods research was conducted on Emirati higher education institutions. Quantitative data was gathered through electronically distributed surveys with 329 faculty members. On the other hand, qualitative data was collected through electronically distributed questionnaires among 14 faculty members. The software used for quantitative data analysis is SPSS. On the other hand, the analysis technique used for the qualitative data involved coding the data and categorizing them into themes. The key findings of the study were that technology integration is beneficial and the BBL is a suitable tool to be used in higher education. It was integrated into the teaching practices by the faculty members to a great extent during the quarantine period (COVID-19). Some external factors such as connectivity proved to be a major challenge to the faculty’s daily teaching practices. Faculty members witnessed some obstacles whilst using BBL such as lack of student's readiness, lack of faculty readiness, and connectivity issues. The implications of the study were the following – the faculty member’s contributions, the technical skills and the training for both faculty members and students in higher education as well as their motivation and readiness are essential in order to ensure effective utilization of BBL. The limitation of the study included the lack of the student’s perspective, the failure of some faculty members to give a detailed response, and the consideration of one higher education institution rather than including several different institutions. This study claims that regardless of the data analysis, there were some challenges and improvement areas to be considered for the effective implementation of BBL. The scope of further study can be an investigation of the impact of COVID-19 on technology integration.